Analisis Pdrb Kabupaten Kebumen Sektor Perdagangan, Hotel Dan Restoran Atas Dasar Harga Berlaku Tahun 2008-2013 - Yulianto (Media Wisata, 2015)
Gross Regional Domestic Product is as the amount of value-added (add value) that are generated by the entire production unit or in a region or the entire amount is the value of final goods and services produced by the economy of the entire unit within a region in a given period, either on the basis of rates in force or on the basis of constant prices. One GRP District of Kebumen is a sector of trade, hotels and restaurants which is an important part of the calculation and the increasing economic growth each year has increased, although not significantly.On the trade sector, the hotel and restaurant viewed from the results of analysis calculation on equation trend for certain years have elevated the quality of the year 2008 amounting to 583, 253.02 in 2009 amounted to 651, 473.61, then increment level trends in2010 719, 694.20, while for the year 2011 for the highest rate of increase in trends, namely of 856, 135.38, then in 2012 has increased the trend 355.97 924, and 2013 for trends 992,576.56.The result of the analysis of the Gross Domestic Product has increased fromKebumen Regency, trade, hotels and restaurants on the basis of the applicable rates in 2008-2013.